A case of pulmonary emphysema showing a dramatic clinical improvement by lung volume reduction surgery - Ninomiya, Hironori; Yamamoto, Nobuharu; Shirakusa, Takayuki (Nihon Kokyuki Geka Gakkai zasshi (Kyoto, 1992), 2004)
A 60-year-old man was admitted to our hospital with exertional dyspnea due to chronic obstructive pulmonary disease. Medicinal treatment had been given previously, but it was not effective. Chest X-ray showed flattening of the diaphragm and hyperlucency of the lung field. Chest CT scan revealed emphysematous change dominantly seen in the upper part of the lungs. Ventilation-perfusion scanning presented an inhomogenous pattern of the disease. Thoracoscopic lung volume reduction surgery (LVRS) was performed. After the procedure, FEV1.0 increased significantly but the symptoms did not improve subsequently. Drainage of persistent pleural effusion was performed, and pulmonary artery pressure elevated. Treatment for heart failure improved his respiratory status dramatically, and he is now in good health without oxygen therapy at five months after operation. He is thoroughly satisfied with the results.